Exploring abstract, physical, social and embodied space: developing an approach for analysing museum spaces for young children. Issue 5 (3rd September 2018) - Hackett, Abigail; Procter, Lisa; Kummerfeld, Rebecca
ABSTRACT: This paper describes a collaboration between museum staff and university researchers to develop a framework for analysing museum spaces from the perspective of young children. The resultant APSE (abstract, physical, social and embodied) framework draws on spatial theories from childhood studies and architecture to consider children's museum visiting from a spatial perspective. Starting with space not only foregrounds the role places, objects and bodies play in how experiences are constituted, but also resists linearity and predictability of mainstream educational policy discourses about young children's learning. As place, children and objects entangle together, they design and make one another. We draw upon Massey's description of the 'chance of space', in which people, objects and places become entangled in unpredictable and unknowable ways, to consider the potential of the APSE framework to offer alternative framings of children in museums.